Banning traditional birth attendants from conducting deliveries: experiences and effects of the ban in a rural district of Kazungula in Zambia. Issue 1 (December 2016) - Cheelo, Chilala; Nzala, Selestine; Zulu, Joseph
Abstract Background In 2010 the government of the republic of Zambia stopped training traditional birth attendants and forbade them from conducting home deliveries as they were viewed as contributing to maternal mortality. This study explored positive and negative maternal health related experiences and effects of the ban in a rural district of Kazungula. Methods This was a phenomenological study and data were collected through focus group discussions as well as in-depth interviews with trained traditional birth attendants (tTBAs) and key informant interviews with six female traditional leaders that were selected one from each of the six zones. All 22 trained tTBAs from three clinic catchment areas were included in the study. Content analysis was used to analyse the data after coding it using NVIVO 8 software. Results Home deliveries have continued despite the community and tTBAs being aware of the ban. The ban has had both negative and positive effects on the community. Positive effects include early detection and management of pregnancy complications, enhanced HIV/AIDS prevention and better management of post-natal conditions, reduced criticisms of tTBAs from the community in case of birth complications, and quick response at health facilities in case of an emergency. Negatives effects of the ban include increased work load on the part of health workers, high cost for lodging at health facilities and traveling to health facilities, as well as tTBAs feeling neglected, loss of respect and recognition by the community. Conclusion Countries should design their approach to banning tTBAs differently depending on contextual factors. Further, it is important to consider adopting a step wise approach when implementing the ban as the process of banning tTBAs may trigger several negative effects.